Resilience of Spanish Firms: a comparative analysis of large and small businesses in the face of 008 financial crisis and COVID-19 - Jose Sevilla; Cristina Ruiz-Martin; Juan Jose Nebro; Adolfo Lopez-Paredes (International Journal of Production Management and Engineering)
The global impact of the COVID-19 crisis has revealed divergent outcomes for businesses, with large corporations thriving while small companies facing challenges. Analyzing the Spanish market, which relies heavily on tourism and lacks large international companies, challenges conventional analyses. Despite these anomalies, business closures align with global trends. Applying the dynamic organizational resilience model—Absorption, Adaptation, and Learning—we propose that large Spanish companies, having weathered the 2008 financial crisis, were better equipped for COVID-19. This article investigates whether deploying organizational resilience justifies the Spanish market's response, exploring the influence of company size and crisis type on survival capacity between 2007 and 2023.